147k views
5 votes
If f(x) = 2x + 3 and g(x) = 3x - 9, find f(g(x)).

User Tim Ramsey
by
5.7k points

2 Answers

7 votes

Answer:


\boxed{\sf f(g(x)) = 6x -15 }

Given:


\sf f(x) =2x + 3 \\ \sf g(x) = 3x - 9

To find:


\sf f(g(x))

Explanation:


\sf Evaluate \ f(g (x)) \ by \ substituting \ in \ the \\ \sf value \ of \ g(x) \ into \ f(x): \\ \sf f(3x - 9) = 2(3x - 9) + 3 \\ \\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \sf = (2 * 3x) - (2 * 9) + 3 \\ \\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \sf = 6x - 18 + 3 \\ \\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \sf = 6x - 15

User Heshjse
by
5.7k points
6 votes

Answer:

6x-15

Step-by-step explanation:

First plug in 3x-9 for x

2(3x-9) +3

Multiply 2 by (3x-9)

2(3x-9)=6x-18

add 3

6x-18+3=6x-15

hope this helps :)

User Sergtk
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.